Angkatan Belia Islam Malaysia (ABIM) membership management system - Hussin, Husnayati; Musa, Amila Norjihah; Wan Ahmad Puad, Wan Nur Asma (IIUM Press, 2011)

(untitled)
This project involves analyzing and designing a prototyping system that automates the membership online system of Malaysian Islamic Youth Movement (ABIM). The primary objective is to create a web-based membership system that will help ABIM's administrator to collect and store members' information in efficient and reliable way as well as to manage the database efficiently. The system will enable the user to do online registration, manage the payment fee, view the activity and muktamar report as well as update their personal detail. It also enables the admin to track members' infonnation, view the payment, activity, muktamar and also membership database. The system is developed using PHP and MySQL